Verticalização da cadeia de suprimentos reversa: um estudo de uma central de comercialização de resíduos sólidos urbanos - Campos, Vinicius Marques (2017)
In the current moment of accomplishments of global agreements in favor of the environment, it is observed the prioritization of the correct management of solid waste. In this sense, the selective collection, recycling and reverse logistics, through partnerships between companies and cooperatives are recurrent issues and in recent years the reverse logistics being driven by the Packaging Sector Agreement in General. In addition, it has been emphasized that the inclusion of waste pickers in this process must take place in a dignified and professional manner. However, as in Londrina, the current scenario has promoted the fall in the average income of these, among other effects. The purpose of this paper was to describe the implementation of an enterprise of the verticalization of the reverse supply chain of post-consumer packages with emphasis on economic aspects. For this, as a methodological proposal, the following research was established: exploratory and descriptive, with bibliographical research, documentary and case study, since an attempt was made to understand the CVMR-LD implementation process for its later description and its effects in the cooperatives of pickers, by means of the construction of five projected scenarios. For each of the first two scenarios, based on decentralized marketing, the economic performance of the cooperatives and the average income of the pickers were estimated. In the other three scenarios, the CVMR-LD cash flow and the NPV, IRR, Payback and Breakeven point indicators were projected, considering different growth rates in the scenarios. In the fourth and fifth scenarios, scenarios 1 and 2 were reconstructed, considering then the operation of the Central and its positive effects on the gain of the cooperative. In addition, current economic issues of Londrina waste pickers cooperatives were analyzed and a brief report of the challenges and opportunities linked to the implementation of the CVMR-LD was produced. The following results were obtained: a detailed description of the characteristics of the CVMR-LD and the report related to the installation of the plant. As for the scenarios, the results were: Scenario 2, with maximum productive growth, presented the best results of a combination of economic sustainability and income of up to R$ 769.02, mainly for maintaining a safety financial margin between sales revenue and the apportionment, through the model that adds 50% of the annual results to the current practice of composition of the apportionment; Scenario 5 presented the best economic indicators of the CVMR-LD, NPV of R$ 11.6 million, IRR of 74.45% pa, Payback of less than 2 years and PE R $ 1.0 million per year in approximate values, Keeping the model more positive that of Scenario 2 with this characteristic, with remuneration of up to R$ 1.156,29.